2015
DOI: 10.1097/aln.0000000000000762
|View full text |Cite
|
Sign up to set email alerts
|

Brain Maturation in Neonatal Rodents Is Impeded by Sevoflurane Anesthesia

Abstract: Background A wealth of data shows neuronal demise after general anesthesia in the very young rodent brain. Here we apply proton magnetic resonance spectroscopy (1HMRS), testing the hypothesis that neurotoxic exposure during peak synaptogenesis can be tracked via changes in neuronal metabolites. Methods 1HMRS spectra was acquired in the brain (thalamus) of neonatal rat pups 24- and 48 h after sevoflurane exposure on post-natal day (PND) 7 and 15, and in unexposed, sham controls. A repeated measure ANOVA was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…A decreased concentration of NAA may reflect neuronal dysfunction or neural death . Therefore, the group independent decrease in NAA may be due to neuronal effects of anesthesia itself, in accordance with previous studies performed in humans and mice . However, the decrease in NAA was more pronounced with HT.…”
Section: Discussionsupporting
confidence: 88%
“…A decreased concentration of NAA may reflect neuronal dysfunction or neural death . Therefore, the group independent decrease in NAA may be due to neuronal effects of anesthesia itself, in accordance with previous studies performed in humans and mice . However, the decrease in NAA was more pronounced with HT.…”
Section: Discussionsupporting
confidence: 88%
“…3,6,7 Sevoflurane is commonly used in clinical anaesthesia for patients of all ages due to its low blood-gas partition coefficient and low metabolic breakdown. 9 Decreased connectivity between excitatory neurons in the prefrontal cortex has been shown to be correlated with cognitive impairments induced by sevoflurane. For example, Makaryus reported that sevoflurane has neurotoxic effects on the development of brain.…”
Section: Introductionmentioning
confidence: 99%
“…Given the potential issue of public mental health and social stability, identifying the links between general anesthesia and impulse control disorder is now of paramount importance. Sevoflurane, the most commonly used pediatric anesthetic, has been shown to act as a neurotoxin affecting synaptogenesis and neuronal morphology in animal studies 12,13 . Therefore, we hypothesize that exposure of the immature brain to sevoflurane may induce ADHD-like behavior conditions in later adulthood.…”
Section: Introductionmentioning
confidence: 99%